2017
DOI: 10.1101/214700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A common allele in FGF21 associated with preference for sugar consumption lowers body fat in the lower body and increases blood pressure

Abstract: word summaryFibroblast Growth Factor 21 (FGF21) is a hormone that induces weight loss in model organisms. These findings have led to trials in humans of FGF21 analogues with some showing weight loss and lipid lowering effects. Recent genetic studies have shown that a common allele in the FGF21 gene alters the balance of macronutrients consumed but there was little evidence of an effect on metabolic traits. We studied a common FGF21 allele (A:rs838133) in 451,099 people from the UK Biobank study. We replicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…However, while changes in caloric intake can affect body weight and metabolic homeostasis, changes in macronutrient intake alone can affect insulin signaling, cardiometabolic health, and longevity (122). Importantly, an additional study using data from 451,000 individuals in the UK Biobank found that not only is the rs838133 allele associated with higher carbohydrate intake but it is also associated with stronger effects on body fat distribution and higher blood pressure than with effects on body mass (40). Thus, FGF21 may regulate nutrient homeostasis and metabolic health beyond changes in body weight.…”
Section: Regulation Of Macronutrient Intake and Sweet Taste Preference By Fgf21mentioning
confidence: 99%
“…However, while changes in caloric intake can affect body weight and metabolic homeostasis, changes in macronutrient intake alone can affect insulin signaling, cardiometabolic health, and longevity (122). Importantly, an additional study using data from 451,000 individuals in the UK Biobank found that not only is the rs838133 allele associated with higher carbohydrate intake but it is also associated with stronger effects on body fat distribution and higher blood pressure than with effects on body mass (40). Thus, FGF21 may regulate nutrient homeostasis and metabolic health beyond changes in body weight.…”
Section: Regulation Of Macronutrient Intake and Sweet Taste Preference By Fgf21mentioning
confidence: 99%
“…Sample quality control (QC) measures included removing individuals who were duplicated and highly related (3rd degree or closer), had sex mismatches, as well as those identified to be outliers of heterozygosity and of non-European descent. Further details of the QC measures applied and imputation performed have been described previously [18][19][20][21].…”
Section: Genotyping -mentioning
confidence: 99%
“…The standard errors (SE) of these estimates were adjusted using the first term of the delta method expansion for the variance of a ratio, allowing for the uncertainty in the first regression stage to be taken into account [24]. Genetic principal components (as previously described [20][21][22]) were included as covariates in the analysis to control for residual population structure. UK Biobank analysis also controlled for the platform used to genotype the samples.…”
Section: Mendelian Randomization Analysismentioning
confidence: 99%
“…However, while changes in caloric intake can affect body weight and metabolic homeostasis, changes in macronutrient intake alone can affect insulin signaling, cardiometabolic health and longevity [62]. Importantly, an additional study using 451,000 individuals from the UK Biobank found that not only is the rs838133 allele associated with higher carbohydrate intake, but it is also associated with stronger effects on body fat distribution and higher blood pressure than with effects on body mass [63]. Thus, FGF21 may regulate nutrient homeostasis and metabolic health beyond changes in body weight.…”
Section: Regulation Of Macronutrient Intake and Sweet Taste Preferencmentioning
confidence: 99%
“…FGF21 also regulates alcohol intake. The FGF21 rs838133 variant associates with increased alcohol intake [63] and the rs11940694 SNP in the β-Klotho (KLB) locus associates with alcohol consumption [76]. Interestingly, administration of recombinant FGF21 [76] or overexpression of FGF21 [71] significantly reduced alcohol preference, but not plasma ethanol concentrations.…”
Section: Alcohol Fgf21 and Liver Functionmentioning
confidence: 99%